Anaesthesia for the Growing Brain - Raviraj, Divya; Engelhardt, Thomas; Hansen, Tom G. (Current Pharmaceutical Design, 2019)
Despite the long history of paediatric anaesthesia, there is still much to be discovered regarding how exposure to anaesthesia affects the developing brain. Given that commonly used anaesthetic agents are thought to exert their effect via N-Methyl-D-Aspartate (NMDA) and gamma-aminobutyric acid A (GABAA) receptors, it is biologically plausible that exposure during periods of vulnerable brain development may affect long term outcome. There are numerous animal studies which suggest lasting neurological changes. However, whether this risk also applies to humans is unclear given the varying physiological development of different species and humans. Human studies are emerging and ongoing and their results are producing conflicting data. The purpose of this review is to summarize the currently available evidence and consider how this may be used to minimize harm to the paediatric population undergoing anaesthesia.
Keywords: neurocognition